2020
DOI: 10.1101/2020.11.02.20221622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproducibility and sensitivity of 36 methods to quantify the SARS-CoV-2 genetic signal in raw wastewater: findings from an interlaboratory methods evaluation in the U.S.

Abstract: In response to COVID-19, the international water community rapidly developed methods to quantify the SARS-CoV-2 genetic signal in untreated wastewater. Wastewater surveillance using such methods has the potential to complement clinical testing in assessing community health. This interlaboratory assessment evaluated the reproducibility and sensitivity of 36 standard operating procedures (SOPs), divided into eight method groups based on sample concentration approach and whether solids were removed. Two raw waste… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 28 publications
10
72
0
Order By: Relevance
“…The notion that currently deployed methods can reliably distinguish lesser from greater amounts of viral surrogates at the conditions investigated is also supported. These inferences are largely consistent with other international studies performed in parallel ( Pecson et al., 2020 ; Pocock et al., 2020 ). Both of these parallel studies concluded that sample preparation methods did not have a clear, systematic impact on results ( Pecson et al., 2020 ; Pocock et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The notion that currently deployed methods can reliably distinguish lesser from greater amounts of viral surrogates at the conditions investigated is also supported. These inferences are largely consistent with other international studies performed in parallel ( Pecson et al., 2020 ; Pocock et al., 2020 ). Both of these parallel studies concluded that sample preparation methods did not have a clear, systematic impact on results ( Pecson et al., 2020 ; Pocock et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…These inferences are largely consistent with other international studies performed in parallel ( Pecson et al., 2020 ; Pocock et al., 2020 ). Both of these parallel studies concluded that sample preparation methods did not have a clear, systematic impact on results ( Pecson et al., 2020 ; Pocock et al., 2020 ). Remarkably, there is substantially less variability in the results amongst the methods deployed in this study than that observed in the parallel study of 36 methods ( Pecson et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations